Sort by

- Relevance
- |Time

**r**= (0.001 * t^4 - 4t + 100)^(1/2)**r**^2 = 0.001 * t^4 - 4t + 100 2r * dr/dt = 0.001 * 4 * t^3 - 4 dr/dt...004 * t^3 - 4 4 = 0.004 * t^3 4 / 0.004 = t^3 1000 = t^3 10 = t**r**^2 = 0.001 * t^4 - 4t + 100**r**^2 = 0.001 * 10000 - 4 * 10 + 100**r**^2...3 Answers · Science & Mathematics · 23/12/2015

lim ((a^

**r**+ b^**r**)/2)^(1/**r**) (as**r**--> 0) LN lim = lim LN lim LN ((a^**r**+ b^**r**)/2)^(1/**r**) = = lim (1/**r**)LN ((a^**r**+ b^**r**)/2) (as**r**--> 0) is...3 Answers · Science & Mathematics · 15/10/2012

**r**(x) is the function "**r**" when the variable "x" in unknown. If the equation...this same principle, (s o**r**) (3), which can also be written as s(**r**(3)) is solved in the following manner. ...2 Answers · Science & Mathematics · 16/07/2012

**r**- 5 = 6.2**r**= 6.2 + 5**r**= 11.26 Answers · Science & Mathematics · 07/11/2010

The answer is

**r**= -.5 I didn't know if you wanted the explanation or not but I...: 2r=-1 Divide 2r by both sides and the answer is**r**=-1/2 or -.52 Answers · Science & Mathematics · 14/10/2010

Since

**r**^2 = (-**r**)^2, we can assume without loss of generality that**r**≥ 0. For each fixed**r**≥ 0, A(**r**) is a circle centered at (0, 0) with radius**r**. (When**r**= 0, then A(0) is simply {(0, 0)}.) Hence...1 Answers · Science & Mathematics · 27/03/2012

I = (2V/

**R**) + 2r I - (2V/**R**) = 2r**r**= (1/2) * [I - (2V/**R**... - IR**r**= (2V - IR) / 2I**r**= (V/I) - (**R**/2)3 Answers · Science & Mathematics · 16/01/2014

**R**is an equivalence relation on R² follows from the fact that equality is an equivalence relation on R¹. (a; b)**R**(a; b) since a=a, so**R**is reflexive if (a; b)**R**(c; d) then...2 Answers · Science & Mathematics · 20/10/2012

An ideal in

**r**is a subset I of**r**such that, for any element x in**r**and any element i...become easier to check. For (a), if we take any function y(x) from**r**and any function z(x) from the proposed subset, we see that for x = 1, z(x...1 Answers · Science & Mathematics · 05/03/2012

f(

**r**) = |(**r**- 2)(**r**- 1)|. As a piecewise defined function f(**r**) = (**r**- 2)(**r**- 1) if**r**≤ 1 or**r**≥ 2 f(**r**) = -(**r**- 2... that f ' isn't defined at**r**= 1. f has three critical values on the...1 Answers · Science & Mathematics · 27/06/2013